Two perfectly conserved arginine residues are required for substrate binding in a high-affinity nitrate transporter - Unkles, Shiela E. (National Academy of Sciences, 2004)
This study represents the first attempt to investigate the molecular mechanisms by which nitrate, an anion of significant ecological, agricultural, and medical importance, is transported into cells by high-affinity nitrate transporters. Two charged residues, R87 and R368, located within hydrophobic transmembrane domains 2 and 8, respectively, are conserved in all 52 high-affinity nitrate transporters sequenced thus far. Site-directed replacements of either of R87 or R368 residues by lysine were found to be tolerated, but such residue changes increased the K(m) for nitrate influx from micromolar to millimolar values. Seven other amino acid substitutions of R87 or R368 all led to loss of function and lack of growth on nitrate. No evidence was obtained of R87 or R368 forming a salt-bridge with conserved acidic residues. Remarkably, the phenotype of loss-of-function mutant R87T was found to be alleviated by an alteration to lysine of N459, present in the second copy of the nitrate signature (transmembrane domain 11), suggesting a structural or functional interplay between residues R87 and N459 in the three-dimensional NrtA protein structure. Failure of the potential reciprocal second site suppressor N168K (in the first nitrate signature copy of transmembrane domain 5) to revert R368T was observed. Taken with recent structural studies of other major facilitator superfamily proteins, the results suggest that R87 and R368 are involved in substrate binding and probably located in a region of the protein close to N459.